Length-weight relationship and diet of the catfish Cambeva guareiensis (Siluriformes; Trichomycteridae) - Ribeiro, Felipe H. N. P.; Bonan, Maria E. P.; Silva, José Lucas Dias da; Azevedo-Santos, Valter M.; Manoel, Pedro S.; Brambilla, Eduardo M.; Silva, Carolina V. (Biota Neotropica, 2021)
Abstract: The length-weight relationship (LWR) and diet of a small trichomycterid catfish, Cambeva guareiensis, was studied based on 58 specimens captured in Corrente stream, Guareí River basin, São Paulo, Brazil. LWR analyses showed values of a ranged from 0.0097 to 0.0149 and b from 2.858 to 3.250. The analysis of the diet showed that high amounts of aquatic insects (93.75% of total items) were consumed by the species. In addition, we found no statistically significant differences when comparing the diet between the dry and rainy periods. Our study contributes to the knowledge on populational biology and feeding ecology of trichomycterid fishes in Brazilian streams.